2017
DOI: 10.3803/enm.2017.32.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into Insulin-Like Growth Factor Binding Protein 2 Transcriptional Regulation

Abstract: Insulin-like growth factor binding proteins (IGFBPs) are major regulators of insulin-like growth factor bioavailability and activity in metabolic signaling. Seven IGFBP family isoforms have been identified. Recent studies have shown that IGFBPs play a pivotal role in metabolic signaling and disease, including the pathogenesis of obesity, diabetes, and cancer. Although many studies have documented the various roles played by IGFBPs, transcriptional regulation of IGFBPs is not well understood. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…IGFBP-2 has been suggested as a biomarker for metabolic diseases, such as diabetes and insulin resistance [33]. In our study, IGFBP-2 concentrations were until 6-fold higher in patients, compared with controls.…”
Section: Discussionsupporting
confidence: 48%
“…IGFBP-2 has been suggested as a biomarker for metabolic diseases, such as diabetes and insulin resistance [33]. In our study, IGFBP-2 concentrations were until 6-fold higher in patients, compared with controls.…”
Section: Discussionsupporting
confidence: 48%
“…In mammals, Igfbp-2 is highly expressed during embryonic stages, and more lowly expressed in adult tissues, with highest levels in liver, adipocytes, the central nervous and reproductive systems, heart, and kidney ( 75 ). Mice embryos overexpressing Igfbp-2 show a reduced growth rate, likely through reduced Igf availability ( 76 ).…”
Section: Physiological Roles Of Teleost Igfbpsmentioning
confidence: 99%
“…Medical interventions focusing on increasing caloric intake fail to counteract wasting (Fearon et al, 2012;Op den Kamp et al, 2009). Importantly, clinical work in humans has shown that cachexia and other disease conditions are associated with elevated levels of IGFBPs (Baxter, 2014;Huang et al, 2016;Shin et al, 2017).…”
Section: Insulin Signalingmentioning
confidence: 99%